Monsoon hysteresis reveals atmospheric memory - Anja Katzenberger; Anders Levermann (Proceedings of the National Academy of Sciences, 2025)
Within Earth’s climate system, the ocean, cryosphere, and vegetation exhibit hysteresis behavior such that their state depends on their past and not merely on their current boundary conditions. The atmosphere’s fast mixing time scales were thought to inhibit the necessary memory effect for such multistability. Here, we show that moisture accumulation within the atmospheric column generates hysteresis in monsoon circulation independent of oceanic heat storage and yields two stable atmospheric states for the same solar insolation. The dynamics of monsoon rainfall is thus that of a seasonal transition between two stable states. The resulting hysteresis is shown in observational data and reproduced in a general circulation model where it increases with decreasing oceanic memory and exhibits the two distinct states that persist for more than 60 y. They are stabilized by moisture accumulation within the atmospheric column that carries information across time scales much longer than those typical for mixing. The possibility of abrupt shifts between these two states has implications for the future evolution of global monsoon rainfall that is crucial for the agricultural productivity currently feeding more than two billion people.